Influence of coffee berries drying in different types of terraces, during different storage periods, on coffee quality - Reinato, Carlos Henrique Rodrigues; Borém, Flávio Meira; Silva, Pablo José da; Oliveira, Eduardo Carvalho (Coffee Science - ISSN 1984-3909)
Physicochemical and sensorial alterations during storage of coffee berries submitted to different processing and drying methods was investigated. The treatments consisted of four types of berries preparation (“roça”, husked berry, berry + green, and floats), three types of drying terraces (concrete, rutty ground and asphalt mud), and two berry drying layer thickness on terraces (thin and thick), in a complete randomized design and a 4 x 3 x 2 factorial scheme. in four storage duration periods. Two replicates per treatment were used. After drying of the berries, the experimental units were split in four, packed into jute bags, and placed into wooden boxes inside a storehouse filled with coco coffee. Treatments were stored for one year. Sampling was accomplished at 4-month internvals but the first one, which was done right after drying of the berries. For evaluation of quality, the following analyses were accomplished: potassium leaching, electric conductivity, total sugars, cup test and counts of black, green and bitter, and black green defects. The results indicate that drying in thick layer has the greatest influence in quality loss during storage, among the factors investigated. It was also found that berries dried on earthen terrace influenced negatively their storability; on the other hand, when the drying process was made on asphalt mud and concrete terraces, no influence was detected on the quality of coffee during storage.